Capacidades dessortivas em cooperativas agropecuárias de produção do Rio Grande do Sul: um estudo sobre a contribuição das capacidades absortivas e inovação aberta - Silva, Vinícius Radetzke da (2024)
In a scenario of constant change in Brazilian agribusiness, it is necessary to develop capabilities to recognize, gather and absorb information from the external environment, as well as to propose strategies to explore, transform and accelerate innovation within cooperatives and, thus, enable an alternative to the economic vitality of the cooperative business. In view of this, this thesis argues that the practices of potential and realized absorptive capacities, combined with the establishment of open innovation, contribute to the development of desorptive capacities in agricultural production cooperatives in Rio Grande do Sul-RS. The thesis aimed to analyze how the implementation of open innovation practices and absorptive capacities contribute to the development of desorptive capacities in agricultural production cooperatives in RS. To this end, a qualitative-quantitative, exploratory-descriptive study model is proposed, based on multiple cases, with a single instrument translated and adapted from thematic scales of absorptive, desorptive capacities and open innovation, aimed at managers of the eight largest agricultural production cooperatives in RS, according to a ranking that measures the Weighted Value of Magnitude (VPG). In the statistical analysis, the Software Statistical Package for the Social Sciences-26 (SPSS) is used for data (mean, median, mode) and inferential (hypothesis tests such as t-tests, ANOVA, correlation and regression tests). The results validated and rejected hypotheses, indicating that absorptive capacities, especially those linked to exploration, when combined with open innovation practices, create an environment conducive to the formation of desorptive capacities in the cooperatives studied. These results refer to an analysis based on data from eight cooperatives and, therefore, require further studies in order to corroborate or refute them. The study favors the exchange of knowledge and practices between cooperatives and their partners, which is crucial for adaptation and innovation in the agricultural cooperative sector, in addition to contributing to the literature on theories of dynamic capabilities and innovation applied to cooperative management. The results provide support for the formulation of strategies aimed at developing the organizational capabilities of these cooperatives, as an alternative to competition and innovation. Therefore, based on the results of the study, it is possible to answer the thesis question, by confirming that both absorptive capacities and open innovation favor the occurrence of processes that are related to desorptive capacities in the agricultural production cooperatives investigated in this study.